Trapezio-metacarpal arthritis: The price of an opposable thumb! - Turker, Tolga (Medknow Publication, 2011)
Trapezio-metacarpal arthritis is the most common arthritic problem of the hand for which patients seek surgical treatment. The current article reviews the etio-pathogenesis, epidemiology, classification and management of this widespread problem. The anatomy and unique biomechanics of this joint are also reviewed. In addition, the article provides a detailed description of our preferred method of trapezio-metacarpal arthroplasty.